2011
DOI: 10.1007/s11771-011-0879-z
|View full text |Cite
|
Sign up to set email alerts
|

Inverse synthetic aperture radar imaging based on sparse signal processing

Abstract: Based on the measurement model of inverse synthetic aperture radar (ISAR) within a small aspect sector, an imaging method was presented with the application of sparse signal processing. This method can form higher resolution inverse synthetic aperture radar images from compensating incomplete measured data, and improves the clarity of the images and makes the feature structure much more clear, which is helpful for target recognition. The simulation results indicate that this method can provide clear ISAR image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…: reconstruct the clean speech magnitude spectrum with (15), (16) and (17). 7: obtain the reconstructed speech signal x in time domain via inverse discrete Fourier transformation with the reconstructed magnitude and the noisy speech phases ζ 1 , …, ζ M .…”
Section: Sparse Reconstruction Based On Adapted Srementioning
confidence: 99%
See 2 more Smart Citations
“…: reconstruct the clean speech magnitude spectrum with (15), (16) and (17). 7: obtain the reconstructed speech signal x in time domain via inverse discrete Fourier transformation with the reconstructed magnitude and the noisy speech phases ζ 1 , …, ζ M .…”
Section: Sparse Reconstruction Based On Adapted Srementioning
confidence: 99%
“…Recently, sparse representation has attracted much attention and is widely used in compressed sensing [15], image [16] and audio signal processing [17][18][19][20].The objective of sparse representation is to represent the most information of a signal with a linear combination of only a small number of atoms. Recent results have indicated that many signals, including the speech signal, can be approximated sparsely [17], which provides a new avenue for the quasi-clean speech construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical features include physical size and scattering structure which can only be obtained by wideband and polarization radar. The physical size can be extracted from high resolution range profile (HRRP) [3], inverse synthetic aperture radar (ISAR) image [4] and three-dimensional image [5], while the HRRP is the easiest one.…”
Section: Introductionmentioning
confidence: 99%